2008
DOI: 10.1097/jto.0b013e3181653c8c
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Radioresponse of Preoperatively Irradiated Invasive Thymomas

Abstract: This modality at modest doses was macroscopically and histopathologically effective on tumors particularly in WHO B1 and B2 thymomas than WHO B3 thymoma. The therapeutic benefit of preoperative RT followed by surgery and postoperative RT for stage III thymomas should be defined thoroughly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 40 publications
(59 reference statements)
0
37
0
2
Order By: Relevance
“…Onuki ve ark. 'nın (30) çalışmasında, evre III, 21 hastaya 12-20 Gy RT uygulanmış, B1 ve B2 histolojik tipde %76 olmak üzere tüm histolojik tiplerde %30 tümör redüksiyonu saptanmıştır. Primer RT definitif olarak ancak anrezaktabl ileri evre hastalıkta yapılabilir.…”
Section: Discussionunclassified
“…Onuki ve ark. 'nın (30) çalışmasında, evre III, 21 hastaya 12-20 Gy RT uygulanmış, B1 ve B2 histolojik tipde %76 olmak üzere tüm histolojik tiplerde %30 tümör redüksiyonu saptanmıştır. Primer RT definitif olarak ancak anrezaktabl ileri evre hastalıkta yapılabilir.…”
Section: Discussionunclassified
“…Onuki et al reported this phenomenon as radiation-induced histological change, which was prominent in type B1 and type B2 thymomas. 2) This change seems to result from the different radioresponses of the tumor epithelial cells and lymphocytes. 2) However, it is also possible for small biopsy specimens to be inconsistent with the surgical specimen because of tumor heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…III thymoma. 2) Considering the present case, even with the most conformal photon radiation technique, the mean dose to the organs at risk would have been quite high. Due to the physics of an X-ray, many beams are required to irradiate a deep, large tumor using XRT, thereby increasing the irradiation of healthy tissues and organs.…”
Section: Disclosure Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…In unresectable or not completely resectable TET, the effects of neoadjuvant chemotherapy and/or radiation might increase the chance of complete resection. Reportedly, complete resection has been achieved in 57% to 80% of TET following chemotherapy (5-7), 90.5% following radiation therapy (8) and 77% to 80% following chemoradiation (9,10). However, these studies were small including only 10 to 21 patients.…”
mentioning
confidence: 94%